PENGARUH POC KIAMBANG DAN KOMPOS KOTORAN SAPI TERHADAP PERTUMBUHAN BIBIT KAKAO DI TANAH ULTISOL - Elsy Dwi; Rika Fitry; Beny Setiawan (Politeknik Negeri Ketapang, 2025)
Cocoa (Theobroma cacao L.) is an important plantation commodity that contributes significantly to Indonesia’s economy as a major export source after the oil and gas sector. This study aimed to determine the effect of kiambang liquid organic fertilizer (LOF) and cow manure compost on the growth of cocoa seedlings in ultisol soil. The experiment was arranged in a completely randomized design (CRD) with two factors. The first factor was LOF: K0 (without LOF), K1 (120 mL LOF + 880 mL water), K2 (150 mL LOF + 850 mL water), and K3 (180 mL LOF + 820 mL water). The second factor was cow manure compost: S0 (without compost), S1 (200 g/polybag), S2 (250 g/polybag), and S3 (300 g/polybag). Each treatment consisted of three replications, resulting in 48 experimental units with a total of 144 seedlings. The results showed that the application of kiambang LOF at 180 mL + 820 mL water significantly increased seedling height, stem diameter, root volume, and dry weight. Cow manure compost at 300 g/polybag significantly improved all growth parameters, including height, stem diameter, number of leaves, root volume, dry weight, and soil pH. The interaction between kiambang LOF (180 mL) and cow manure compost (300 g/polybag) significantly affected seedling height at 3, 5, and 7 weeks after planting (WAP) and root volume